Immunopathological reactions, endothelial dysfunction and pathological angiogenesis as independent mechanisms of maladaptive left ventricular remodeling in ischemic and nonischemic heart failure patients - Rasputniak, O. V.; Havrylenko, T. I.; Rudenko, K. V.; Ryzhkova, N. O.; Pidhaina, O. A.; Rybakova, O. V.; Zalevskyi, V. P.; Lomakovskyi О. M. (Zaporozhye Medical Journal, 2021)
Regardless of the great progress in studying the heart failure (HF) pathophysiology, the question about involvement of immune cells activation, systemic inflammation, inflammatory cytokine dysregulation and endothelial dysfunction in maladaptive left ventricular (LV) remodeling in ischemic and nonischemic HF patients is still open to discussion. The aim was to study the characteristics of immunopathological reactions (immunoinflammatory and autoimmune), endothelial dysfunction and pathologic angiogenesis in maladaptive LV remodeling in ischemic and nonischemic HF patients. Materials and methods. A total of 20 healthy volunteers, 31 ischemic HF patients (group 1) and 43 nonischemic HF patients (group 2) were enrolled in the study. All the patients underwent coronarography, ventriculography, echocardigraphic examination. The main lymphocyte subset counts (flow cytometry), serum concentration of C-reactive protein (CRP), vascular endothelial growth factor A (VEGF), TNFα, endothelin-1 (enzyme-linked immunosorbent assay (ELISA)), autoantibodies to myocardium and vessels were detected. Results. Regardless of the HF etiology, all the examined patients demonstrated echocardiographic features of maladaptive LV remodeling and severe intracardiac hemodynamic disorders that was associated with immune system activation, namely increased total and subset lymphocyte counts, chronic systemic inflammation (CRP), autoimmune process with an increase in autoantibodies to myocardium and vessels, and endothelial dysfunction (increased endothelin-1 and VEGF). Under-expression of TNF-α combined with over-expression of VEGF seemed to indicate pathological angiogenesis in ischemic and nonischemic HF patients Conclusions. Significantly increased VEGF levels in heart failure patients can be considered as additional integral key marker of immune inflammation, endothelial dysfunction and pathological angiogenesis and may indicate maladaptive cardiac remodeling in severe heart failure.